2 - Sleeping Sickness Epidemic in British Southern Cameroons 1922-1961: The History of a Colonial Medical Response - Michael Kpughe Lang (Afrika Zamani, 2022)
This article examines the engagement of the British colonial administrative and medical officials in the campaign against the sleeping sickness epidemic in Southern Cameroons. The engagement was informed by the disease’s negative bearing on the colonial agenda and involved the implementation of control policies. The campaign had three fronts: treatment in humans, treatment in animals, and efforts to get rid of the tsetse fly. The control measures which overlooked indigenous coping strategies were misdirected, brutal, and flawed. Enforcing these measures involved complex interactions between colonizers, colonial subjects, and local intermediaries. This occasioned socio-economic disruptions and indigenous resistance as livelihoods were depleted. While control measures boosted exploitative colonial investments, they triggered low economic productivity and underdevelopment among the local populations as they were deprived of access to food, travel, trade, and job opportunities outside their communities. This was destructive to communal life, economically painful, and aggregately harmful to indigenous pride, wellbeing, and survival.